Forest patches as stepping stones: evidence from invertebrate taxonomic and functional diversity in experimentally created water-filled tree holes - Gossner, Martin M.; Roth, Nicolas; Rothacher, Julia; Wong, Mark; Schmidl, Jürgen (Ecography, 2025)
Tree-related microhabitats (TreMs), such as water-filled tree holes (WTHs), are important structures for forest biodiversity, providing habitats for many specialized species, which are however impaired by the intensive forest management of the past. Strategies to maintain and promote TreMs in managed forests, e.g. by establishing old-growth forest patches as stepping stones, have been implemented, but their success has rarely been tested. We experimentally created WTHs in old-growth patches that were established to connect forest nature reserves (FNRs) in a beech forest in Germany. Eight years after creation, we sampled, identified, and measured traits of the invertebrate community that colonized the WTHs. We then investigated how spatial and environmental variables affected taxonomic and functional attributes of communities and populations. A total of 2407 individuals of 13 species were sampled, the majority of which were insect larvae. Abundance, as well as taxonomic and functional diversity attributes and community composition, were influenced by environmental and spatial factors, generally supporting the patch-dynamics and species-sorting metacommunity archetype. At the population level, both spatial and environmental factors affected the abundance and functional diversity of body size distributions, suggesting that dispersal capacities, microhabitat requirements, and competitive abilities of individual species structure communities. The distance to the FNRs had a positive effect on total invertebrate abundance and the abundance of the specialized marsh beetle Prionocyphon serricornis, and a weak negative effect on the functional diversity of the community. Our study underpins the stepping-stone concept of connecting FNRs. The species colonized all newly created microhabitats from source populations, indicating that these patches increase connectivity between the FNRs and thus contribute to forest biodiversity conservation. The negative effects of distance to FNRs on functional diversity suggest that distances between habitat patches should be kept small for such a strategy to be successful and sustainable in the long term.
CRIS-Team Scopus Importer:2025-12-05
Keywords: competition; connectivity; dispersal; metacommunity; stepping stones; traits; tree-related microhabitat; water-filled tree holes